An international, multicenter, retrospective study on the positive impact of cutaneous involvement on the clinical outcome of adult T-cell leukemia/lymphoma - Malpica, Luis (2022)
Adult T-cell leukemia/lymphoma (ATLL) is a largely incurable disease. Cutaneous involvement is common and could be first symptom of the disease. We analyzed 169 patients with ATLL of whom 63 had cutaneous involvement. Cutaneous involvement was found in 48, 27, 17, and 60% of acute, lymphomatous, chronic and smoldering ATLL cases, respectively. Eight cases had primary cutaneous tumoral variant. Erythroderma (24%) and plaques (22%) were the most frequent skin lesions. The presence of cutaneous involvement was associated with better overall survival compared to non-cutaneous involvement (aHR 0.55 [95% CI: 0.37–0.82], p < 0.01 1-year OS 53 vs. 27%, respectively, p = 0.012). Combination zidovudine and interferon-alpha (AZT-IFN) yielded high response rates (overall response, OR = 100%, n = 8 complete response 62.5%) compared to chemotherapy (OR = 33.3%, n = 12/36). In conclusion, cutaneous involvement was associated with better survival in Latin American patients with ATLL. AZT-IFN demonstrated encouraging responses in ATLL patients with cutaneous involvement.